Dissimilar titanium-aluminum skin-stringer joints by FSW: process mechanics and performance. Issue 4 (12th March 2023) - Rana, Harikrishna; Campanella, Davide; Buffa, Gianluca; Fratini, Livan
ABSTRACT: Ever since its inception, friction stir welding 1 (FSW) is being validated by scientific investigations as an effective substitution for fusion-based conventional joining technologies. One of the main strengths of FSW is the possibility to produce dissimilar joints, even using materials extremely different in terms of thermal and mechanical properties. The goal of the present research is to investigate the feasibility of both Al-Ti skin-stringer and reversed Ti-Al skin-stringer joints, highlighting the effect of joint configuration and main process parameters on material flow and joint mechanical properties. During the investigation, the essentiality of the proper heat input through balancing GRAPHICAL ABSTRACT: uf0001